(13)C Nuclear Magnetic Resonance Spectroscopy of Native and Recombined Lipoproteins - Assmann, Gerd (1974)
(13)C nuclear magnetic resonance data on native and recombined lipoproteins are reported. [Methyl-(13)C]phosphatidylcholine, [methyl-(13)C]sphingomyelin, 1,2-[dioleoyl-1-(13)C]-sn-phosphatidylcholine and cholesteryl-[1-(13)C]oleate were enriched with 90% carbon-13 in respective molecules by chemical synthesis and used for recombination experiments with high density lipoprotein apoproteins. Relaxation times for these specifically enriched lipids in organic solvents, (2)H(2)O, and lipid-protein complexes isolated by ultracentrifugal flotation, were measured. The results show that both the phosphatidylcholine and sphingomyelin polar headgroups have the same hydrophilic environment in either sonicated lipid particles or reassembled lipoproteins, and suggest that ionic interaction of lipid and apolipoproteins is of minor importance in the formation of plasma lipoprotein complexes. Our experiments indicate that (13)C nuclear magnetic resonance spectroscopy will contribute to the understanding of lipidprotein interaction in lipoproteins and membranes.